A novel optimization method for thermoelectric module used in waste heat recovery. (1st April 2020) - Luo, Ding; Wang, Ruochen; Yu, Wei; Zhou, Weiqi
Highlights: A novel thermoelectric module structure optimization approach for fluid waste heat recovery is proposed. A fluid-thermal-electric multi-physics model is developed to conduct the optimization. Output power between the novel module and the corresponding base module is compared. The optimal value of Δ l is about 0.01 mm for the simplified thermoelectric module. The power output enhancement can be more obvious when more thermoelectric legs are contained. Abstract: When recycling fluid waste heat with thermoelectric devices, the current generated by the thermoelectric module is limited by the minimum current among the thermoelectric legs, which results in electric power losses. To address this issue, a novel optimization method for thermoelectric module structures is first proposed, wherein the length of the thermoelectric legs is determined by their specific temperature differences. Additionally, a fluid-thermal-electric multiphysics model is developed to predict the behaviour of an air-to-water thermoelectric generator system. To reduce the workload, a simplified thermoelectric module is used to conduct the optimization. The results indicate that the fluid-thermal-electric multiphysics model can determine the temperature distributions and voltage distributions of the thermoelectric generator system with acceptable accuracy. The proposed optimization method can effectively improve the output performance of the thermoelectric module. Despite using the same amount of thermoelectric materials, the novel thermoelectric module exhibits a higher output power than the base thermoelectric module structure when Δ l  ≤ 0.03 mm, and the optimal value of Δ l is approximately 0.01 mm for the simplified thermoelectric module. In addition, if the thermoelectric module contains a greater number of thermoelectric legs, the optimization method will provide greater performance enhancements. The proposed optimization method contributes to enhancing the output performance of thermoelectric modules used for fluid waste heat recovery.